What is The Progression of Joint Deformity and Disability in Rheumatoid Arthritis Patients with Different Treatment Approaches? : A Systematic Review - Billy Jonathan; Veronica Winda Soesanto; Chaira Sultana Mazaya (The International Journal of Medical Science and Health Research, 2025)
Introduction: Rheumatoid Arthritis (RA) is a chronic autoimmune disease leading to progressive joint destruction and disability. Modern management has shifted towards early, aggressive "treat-to-target" strategies to halt disease progression. This systematic review evaluates the progression of joint deformity and disability in RA patients under various treatment approaches. Methods: Following PRISMA guidelines, we systematically reviewed randomized controlled trials from PubMed, Springer, Semantic Scholar, and Google Scholar. We included studies on adult RA patients with at least a 12-month follow-up that assessed joint deformity or functional disability. Nine studies met the inclusion criteria for the final analysis. Results: Early, aggressive treat-to-target strategies resulted in minimal radiographic progression, with some studies showing a complete halt in joint damage over long-term follow-up of up to 10 years. Functional disability, measured by the Health Assessment Questionnaire (HAQ), improved across all pharmacological interventions. Non-pharmacological interventions, like complex rehabilitation, significantly improved functional status, reducing HAQ scores by up to 73.8%, but their effect on radiographic outcomes was not reported. Baseline anti-CCP positivity and high disease activity were predictors of poorer outcomes. Discussion: The evidence confirms that early and sustained pharmacological treatment is crucial for controlling structural damage and preserving function. Combining these treatments with non-pharmacological therapies like targeted exercise provides additional functional benefits. However, a gap remains in understanding the impact of non-pharmacological interventions on long-term joint structure. Conclusion: An integrated approach combining early, aggressive pharmacotherapy with adjunctive non-pharmacological interventions offers the most effective strategy for managing RA. This approach successfully limits joint deformity and improves patient disability and quality of life.